Recombinant Human Nerve Growth Factor (Cenegermin)–Driven Corneal Wound Healing Process: An Evidence-Based Analysis - Bonzano, Chiara; Olivari, Sara; Cutolo, Carlo Alberto; Macrì, Angelo; Sindaco, Daniele; Borroni, Davide; Bonzano, Elisabetta; Traverso, Carlo Enrico (Frontiers in Pharmacology, 2022)
Purpose: To evaluate anterior segment optical coherence tomography (AS-OCT) to detect the wound healing process as per monitoring the effectiveness of cenegermin to treat moderate to severe neurotrophic keratoplasty. Methods: A retrospective chart review was realized to identify patients treated with cenegermin at the Clinica Oculistica, University of Genoa, Italy. All patients underwent careful examinations at baseline and follow-up visits. AS-OCT scans centered on the minimum corneal thickness (CT) area were always performed. We compared findings of AS-OCT with the findings from the slit-lamp examination. A linear regression analysis was used to evaluate factors associated with corneal healing. A further analysis, including a control group treated with 50% autologous serum (AS), was done to investigate and compare the efficacy of cenegermin. Results: Data from 16 eyes were studied. The average patients' age was 60.9 ± 21.1 years; five (31.2%) eyes experienced persistent epithelial defect and 11 (68.8%) eyes had neurotrophic corneal ulcer. The average reepithelialization time was 3.9 ± 0.5 weeks in the cenegermin group versus 5.9 ± 1.9 weeks in the AS group (p < 0.01). The AS‐OCT scans revealed an average CT at the thinnest point of 276.3 ± 74.1 μm before treatment with an average increase of 176.5 ± 60.3 μm at the end of the cenegermin treatment (B = −0.15; p = 0.035). The AS-OCT percentage increase in corneal thickness between the two groups was statistically significant (p < 0.02). Conclusion: Understanding the cascade of events involved in the nerve growth factor–driven corneal wound healing process is clinically meaningful for the clinician. AS-OCT is an effective tool for systematic anterior segment imaging, allowing the detailed detection of the front-to-back layered corneal structure for quantitative analysis and monitoring of the healing process.